Household saving behavior: The role of literacy, information and financial education programs - Annamaria Lusardi (Goethe University Frankfurt, Center for Financial Studies (CFS), 2007)
Individuals are increasingly in charge of their own financial security after retirement. But how well-equipped are individuals to make saving decisions; do they possess adequate financial literacy, are they informed about the most important components of saving plans, do they even plan for retirement? This paper shows that financial illiteracy is widespread among the US population and particularly acute among specific demographic groups, such as those with low education, women, African-Americans and Hispanics. Moreover, close to half of older workers do not know which type of pensions they have and the large majority of workers know little about the rules governing Social Security benefits. Lack of literacy and lack of information can affect the ability to save and to secure a comfortable retirement; few individuals rely on the help of financial advisors and ignorance about basic financial concepts can be linked to lack of retirement planning and lack of wealth. Financial education programs can help improve saving and financial decision-making, but much more can be done to improve the effectiveness of these programs.
urn:nbn:de:hebis:30-50990
Keywords: D91; 330; Financial Literacy; Financial Education Programs; Saving Behavior; Pensions; Sparen; Kapitalanlage; Alterssicherung; Informationsverhalten; Bildungsniveau; USA